Penerapan Metode SWOT pada Strategi Pemasaran Penjualan Produk Tirai untuk Customer di CV.Aneka Prima Sukses Abadi - Winda Nurul Azizah; Rizal Rizal (Pusat Riset dan Inovasi Nasional, 2025)
The marketing strategy for selling curtain products for customers is an approach that focuses on consumer needs and preferences. The tactics used include visual promotion through social media, attractive price offers, and consulting services for selecting curtain models and materials that suit the room. Then the purpose of the research carried out from the marketing strategy includes analyzing current problems in the marketing strategy for selling curtain products for customers and formulating solutions as a reference for marketing strategies for selling curtain products in the future. The method used during the research process uses SWOT which has parameters of strengths, weaknesses, opportunities and threats so that the results obtained in the study are marketing analysis with the SWOT method, SWOT strategy and SWOT conclusions.